ANALYSIS OF SUSTAINABILITY OF DEVELOPMENT AND DETERMINATION OF POTENTIAL POINTS / POLES OF GROWTH OF A REGION (ON THE EXAMPLE OF AKTOBE REGION) - Tolkyn A. Azatbek; Daniyar T. Baitenizov; Mira A. Zhanabergenova (Academic Journal of Physical and Chemical Sciences, 2020)
The regions of Kazakhstan have a high growth potential. Its timely assessment and identification of reserves for future sustainable growth makes it possible to develop facilitating mechanism. This research is part of the scientific project “Formation of Growth Poles and Zones of Sustainable Development in Kazakhstan area of the Silk Road Economic Belt”, carried out as part of a grant from the Ministry of Education and Science of the Republic of Kazakhstan. The research methodology is based on classical foreign theories and models of regional economic growth and development, models of macroeconomic analysis, and econometric modeling. The methodology for identifying growth poles is based on the stability of their growth and compiled using various economic indicators of regional development. Through the results of the research we can determine which industries and activities are the driving forces of the regional economy. To determine the growth poles in the region’s economy groups of quantitative and qualitative criteria were used that allowed to identify and justify industries with the highest growth potential, assess sustainability (development trends) and the level of growth of economic activity by industries and districts of the region. Based on the processing of large statistical material, the authors substantiated industries as potential growth poles and activities that are priority for development. Based on the results, the authors ranked industries and activities from the most promising to the least developed. The study provides an opportunity to adjust the economic policy of the region in the long term, taking into account new opportunities, focusing on sustainable development.